Dinamika Serangan Hama Utama pada Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) di Periode Pra-Produksi - Muharram; Parmanoan Harahap; Siti Hardianti Wahyuni (Journal Agro-Livestock, 2024)
This main pest can damage oil palm crops at the unproductive harvest stage (TBM). The purpose of this study is to determine the prevalence of severe pest attacks on non-producing oil palm (TBM) plants. Unproductive crops (TBM) were selected for data collection on the main pest infestation areas. Data from the available regional pest attack observations were obtained by selecting local pest attack data. The observed parameter is the severity of pest attacks in 2022. Observation results show that the rate of rat attacks increases in the dry season, while other pests decrease in the rainy season. From the observation results, it can be concluded that the proportion of damage caused by rats increases in the dry season, while other pests decrease in the rainy season. From June to July, rats (0.35%), horned beetles (0.35%), and yellow beetles (0.15%) were exposed to pests, and from July to August, rats (0.5%) were exposed to horn beetles (0.1%) and beetles. and brown beetles (0.15%). The pest infestation category (rats, horn beetles, and brown beetles) is classified as a light attack.